Passion-fruit shell biomass as adsorbent material to remove chromium III from contaminated aqueous mediums - Campos-Flores, Gaby (2019)
ABSTRACT The aim of the study was to evaluate an adsorbent material based on passion-fruit shell biomass (PFSB) for chromium III removal from contaminated aqueous mediums, composed of distilled water and different concentrations of Cr(III), with a dose of 5 g of PFSB per liter. The residual concentration of Cr(III) in the treated mediums was determined by Atomic Absorption Spectrophotometry. A good adsorption process was carried out, achieving removal levels up to 85, 80, and 53% for solutions of 20, 50 and 200 ppm of Cr(III), respectively. The results showed an adequate fit to Langmuir and Freundlich models (R2 of 0.8864 and 0.7596, respectively), obtaining the following parameters qmax: 27.933 mg g−1and b: 0.029 (for Langmuir model), and k: 1.400 and n: 1.650 (for Freundlich model), with a good adsorbent-adsorbate interaction for Cr(III) according to FT-IR spectra. Therefore, the obtained results suggest that Cr(III) can be removed by more than 50% by using passion-fruit shell, which with a minimum treatment could be used as an adsorbent in the treatment of chromium-contaminated aqueous mediums.